L’informalité urbaine aux marges de la connaissance. Statistiques, cartographie et politiques des bidonvilles à Madrid - Aguilera, Thomas (Anthropologica, 2019)
Informality is usually defined as the whole practices that escape from the state and the radar of the administrations. Yet, informality is not invisible and causes conflicts around the way it is possible to produce knowledge about it. The article, which focuses on slums upgrading policies in Madrid (Spain) since the 1960s, sheds light on urban informality by locating itself at the crossroads of two types of literature: the anthropology of ignorance and the sociology of public policies. It shows how the institutionalization of these resorption policies was based on the constitution of important statistical and mapping devices but that a large part of the phenomenon (the big slum of the Cañada Real Galiana) was deliberately left out of these official public knowledge devices in order to avoid putting on the political agenda what appeared to be a reserve of informality necessary to host of populations evicted elsewhere. It also shows that residents have mobilized to resist this exclusion and produce alternative knowledge about their neighbourhood. The article concludes that shantytowns, and more generally urban informality, are at the crossroads of processes of formalization and informalization that overlap on struggles for the production of knowledge or ignorance.